Increase in the development of Pueraria phaseoloides (tropical Kudzu) due to tolerant acid rhizobia under acidity and low fertility conditions - Hernández, I.; Rosales, P. R.; González, P. J.; Ramírez, J. F.; Nápoles, María; Pérez, Reneé (Cuban Journal of Agricultural Science, 2020)
The effect of acid-tolerant rhizobia isolates on growth, nodulation and yield of tropical kudzu, grown under acidity conditions, was determined. By measuring the diameter of the colony and the number of viable cells, the pH tolerance of three Bradyrhizobium strains: K2, 1_2 and 2_4 was established under acidity conditions. Two inoculation tests of tropical kudzu were carried out: one under controlled conditions, and another in the field. The effect of acidity on nodulation, growth and yield of crop was determined. A simple classification ANOVA and a two-factor arrangement were used in the statistical analysis. The three strains of rhizobia were tolerant at pH 4.5. This condition did not decrease its dispersion in the Petri dish, the diameter of the colonies or the number of viable cells. The acidity did not decrease the nodulation or the growth of kudzu plants, inoculated with K2 and 1_2 under controlled conditions. The inoculation of kudzu with rhizobia isolates produced effectiveness in the biological fixation of nitrogen, more than 90 % of the total nodules, more than 75 % of the aerial dry mass yield, and more than 45 % of the nitrogen content of the aerial biomass of plants, under field conditions. The elaboration and application of inoculants based on K2 and 1_2 would contribute to reducing the use of mineral fertilizers in soils affected by acidity. Key words: Bradyrhizobium, stress, forages, growth.